Desulfurization of Coal with Oak Ash Extraction - Caglayan, Gizem Hazan; Ipek, Ubeyde (Taylor & Francis Inc, 2025)
Desulfurization is an essential method to eliminate the harmful environmental effects of coal. Various physical, chemical and biological desulfurization methods are available in the literature. In this study about with the desulfurization of coal by a basic extraction liquid of oak ash. Burdur, Ermenek and Tun & ccedil;bilek coals were selected due to their high sulfur content. Before and after the desulfurization process; total sulfur, pyritic sulfur, carbon content and calorific value were measured. The highest removal efficiencies of total sulfur and pyritic sulfur for Burdur coal obtained as 41% and 67%, for Tun & ccedil;bilek coal obtained as 41% and 35%, and for Ermenek coal obtained as 47% and 41%, respectively. Furthermore, the carbon and calorific value of these coals were analyzed and it seen that these values were not affected negatively. These findings confirmed that the desulfurization with oak ash of Burdur, Tun & ccedil;bilek and Ermenek coals could help as a reference for further optimizing the coal desulfurization process.
Keywords: desulfurization; coal; oak ash; extraction; air pollution; sulfur